Application of chemometric methods for the voltammetric determination of tryptophan in the presence of unexpected interference in serum samples. (15th July 2020) - Saeidinejad, Faezeh; Ghoreishi, Sayed Mehdi; Masoum, Saeed; Behpour, Mohsen
Highlights: A rapid method based on DPV and PLS for determination of Trp in the presence of Tyr. Surface characterizations of the nanosensor. Application of multivariate optimization strategy with significant time saving. Applicability and ability of the proposed method in real samples. Abstract: An analytical methodology based on differential pulse voltammetry (DPV) on an Au nanoparticles modified carbon paste electrode (AuNPs/CPE) and the partial least-squares (PLS) algorithm for the determination of tryptophan (Trp) in the presence of unexpected electroactive interference, tyrosine (Tyr) with overlapped peaks, in serum samples was described. At first, the synthesized Au nanoparticles were characterized by scanning electron microscopy (SEM) and the suitability of AuNPs/CPE for determination of Trp in the presence of Tyr was checked using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). Then experimental conditions were optimized with central composite rotatable design (CCRD) and response surface methodology (RSM), involving several chemical and instrumental variables. After optimization, the resolution of the two multicomponent mixtures has been accomplished by PLS for voltammmetric studies of Trp. Finally, the proposed method was found to be applicable for the analysis of the Trp in the presence of unexpected interference in serum samples.